2010
DOI: 10.1017/s0007114510001546
|View full text |Cite
|
Sign up to set email alerts
|

Nuts, metabolic syndrome and diabetes

Abstract: The ability of nuts to improve the blood lipid profile and reduce the risk of CHD is now well established. The interest that health effects of nuts have gained recently has brought the possible benefits of consuming nuts, such as improvement in the conditions of the metabolic syndrome, and their potential to prevent and control diabetes into focus. Results from cohort studies have associated nut consumption with a reduced risk of developing diabetes and CVD. However, few randomised controlled trials have asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 66 publications
3
74
1
2
Order By: Relevance
“…The frequency of nut consumption has been inversely related to several chronic prevalent conditions, such as diabetes, hyperlipidemia, hypertension, obesity, metabolic syndrome, cancer, and CHD, among others [5,26]. These inverse associations can be influenced by various mechanisms: nuts improve the blood lipid profile [6] and appear to decrease insulin resistance [8], and there is also evidence suggesting that they can modulate inflammation [35], oxidative stress [36], and endothelial function [37]. As a large body of evidence supports the beneficial effects of frequent nut consumption on many health outcomes, it is plausible that nuts protect as well against all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of nut consumption has been inversely related to several chronic prevalent conditions, such as diabetes, hyperlipidemia, hypertension, obesity, metabolic syndrome, cancer, and CHD, among others [5,26]. These inverse associations can be influenced by various mechanisms: nuts improve the blood lipid profile [6] and appear to decrease insulin resistance [8], and there is also evidence suggesting that they can modulate inflammation [35], oxidative stress [36], and endothelial function [37]. As a large body of evidence supports the beneficial effects of frequent nut consumption on many health outcomes, it is plausible that nuts protect as well against all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of nut consumption was also related to lower rates of sudden cardiac death in a large cohort of men [7]. Furthermore, epidemiologic studies and clinical trials have shown that frequent nut consumption is associated with a reduced load of cardiovascular disease risk factors, such as dyslipidemia, type 2 diabetes, and metabolic syndrome [4,6,8,9]. In addition, reports from the Iowa Women’s Health study [10], a large Dutch cohort [11], and the US Nurses’ Health Study [12], which assessed populations with relatively low overall nut intake, suggested that frequent nut consumption related inversely to total mortality, albeit the protective effect was weak, with adjusted risk reductions ranging from 5% to 15% [10]–[12].…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of their unique composition, nuts are likely to beneficially impact heart health and reduce the incidence of diabetes. Epidemiologic studies have associated nut consumption with a reduced incidence of coronary heart disease in both genders and diabetes in women (Kendall et al 2010;Ros et al 2010). Brazil nuts were found to contain highly variable and often very high concentrations of Se, Ba and Sr (Caglarirmak 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Nuts are a worthwhile inclusion in the diet of patients with metabolic syndrome and diabetes, as data provides support for improved glycemic control and decreased cardiovascular risk [102]. Nut consumption four times a week has been demonstrated to decrease risk for coronary artery disease by 37% based on four large prospective studies [103].…”
Section: Nutsmentioning
confidence: 99%